AMPHOTERICIN B TOPICAL EXTEMPORANEOUS PREPARATIONS FOR THE TREATMENT OF NON-DERMATOPHYTIC ONYCHOMYCOSIS - PHOJANA, KOMESMUNEEBORIRAK; PORNPEN, WERAWATGANONE; WALAISIRI, MUANGSIRI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: At present, the nail preparation to cure onychomycosis, caused by non-dermatophyte molds, is not commercially available in Thailand. The physical and chemical stability of amphotericin B (AmB) extemporaneous preparations in the presence of 30% dimethyl sulfoxide (DMSO) and their in vitro nail permeation was evaluated. Methods: AmB extemporaneous preparations in the presence of 30% DMSO were prepared from a commercial sterile injection product, and cream or hydrophilic ointment. Physical stability was tested at 30°C for 2 months, or using 6 heating-cooling cycles. The chemical stability and in vitro nail permeation of AmB content were analyzed using high-performance liquid chromatography (HPLC). In vitro nail permeation was performed by applying 3.5 mg/mm2 of the tested formulation on nail clippings for 5 consecutive days. Results: The AmB cream and ointment extemporaneous preparations containing 30% DMSO, a permeation enhancer, were homogeneous and pale yellow to yellow cream or ointment. The AmB ointment was stable for up to 60 days. The ointment preparation allows in vitro penetration through nails up to 14.17 μg/cm2. The ointment preparation allows significantly better penetration through than the cream preparation due to the presence of DMSO, sodium lauryl sulfate (SLS), and water in the ointment preparation. Conclusion: The AmB extemporaneous ointment was successfully compounded from a commercial sterile injection product with a beyond-use date of 60 days. The ointment preparation is currently under further investigation for in vivo efficacy.